2017
DOI: 10.1097/ypg.0000000000000172
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of large, rare copy number variants associated with psychiatric and neurodevelopmental disorders in individuals with anorexia nervosa

Abstract: Anorexia nervosa (AN) is a serious and heritable psychiatric disorder. To date, studies of copy number variants (CNVs) have been limited and inconclusive because of small sample size. We conducted a case-only genome-wide CNV survey in 1,983 female AN cases included in the Genetic Consortium for Anorexia Nervosa (GCAN). Following stringent quality control procedures, we investigated whether pathogenic CNVs in regions previously implicated in psychiatric and neurodevelopmental disorders were present in AN cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…CNVs occur when sections of the genome are repeated or deleted and this repetition or deletion varies between individuals. In 2017, the largest CNV survey of AN was conducted [*31]. This report included approximately 2,000 AN cases and examined the prevalence of rare CNVs previously associated with psychiatric and neurodevelopmental disorders.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…CNVs occur when sections of the genome are repeated or deleted and this repetition or deletion varies between individuals. In 2017, the largest CNV survey of AN was conducted [*31]. This report included approximately 2,000 AN cases and examined the prevalence of rare CNVs previously associated with psychiatric and neurodevelopmental disorders.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The adolescent and young adult populations are considerably vulnerable to developing eating disorders and their serious physical and psychosocial consequences [6,7]. Moreover, much epidemiological research specifically focusing on eating disorders has reported that genetic and sociocultural predispositions as well as biological and psychological vulnerabilities play an important role in their development [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A microduplication locus at 15q11.2 was suggested of genetic association with AN with nominal significance (P=0.036), whereas it did not pass correction for multiple testings (Wang et al, 2011). However, a recent case-only study including 1983 cases of AN did not identify this microduplication locus, while genotyping data of the Illumina 660W-Quad SNP arrays (Boraska et al, 2014) and PennCNV were used for the CNV analysis (Yilmaz et al, 2017).…”
Section: Microduplication Of Bp1-bp2 and Anorexia Nervosamentioning
confidence: 99%